Abses Peritonsil Berulang pada Pasien Perokok Aktif - Khoirriyani, Dwi; Benediktus, Adrian (PERHATI-KL, 2025)
Background: Peritonsillar abscess is one of the most common conditions seen in healthcare settings. Serious complications such as airway obstruction may occur if peritonsillar abscess is not treated properly. There are several risk factors that contribute to the development of a peritonsillar abscess, one of which is smoking. Purpose: To analyze the association between the incidence of recurrent peritonsillar abscess in patients who were active smokers. Clinical question: How is recurrent peritonsillar abscess associated with active smoking? Case report: A case of a 43-year-old male patient with recurrent peritonsillar abscess and a history of active smoking, who was treated with drainage incision and was given antibiotics. Method: Evidence-based literature searches were conducted using PubMed, ScienceDirect, and ProQuest using ”peritonsillar abscess” AND ”smoker”. Result: Anatomical changes in the oral cavity and immunologic disorders in active smokers, both systemic and local, predisposed this population to higher risk factors for recurrent peritonsillar abscesses. Conclusion: Peritonsillar abscess could cause serious complications if not diagnosed and treated early. Smoking cessation might prevent recurrence of peritonsillar abscess.